Perencanaan Arsitektur Sistem Informasi Sekolah Menggunakan Metode Togaf di SMK PGRI 35 - Oktaviani, Dewi Asri; Nugraha, M. Fahmi; Trianto, Topan (Ma'soem University, 2024)
In carrying out its activities, SMK PGRI 35 Solokan Jeruk still has difficulties in managing information related to school information systems, so it is necessary to strive for better management of information systems, one of the efforts is through information systems by utilizing computer-based information technology. The purpose of this study is to recommend the development of a school information system architecture in order to achieve success in business process activities that exist within the organization. For the analysis of architectural planning using The Open Group Architecture Framework (TOGAF) method, where there are seven stages carried out in this thesis namely primary, Requirements Management, Architecture Vision, Business Architecture, Information System Architecture, Technology Architecture, Opportunities Solution and Migration Planning. This research produces a principles for creating enterprise architecture, the architectural vision is created. Then produce a blueprint (blueprint) design of the main architecture.